PHYSICO-MORPHOLOGICAL AND FUNCTIONAL ATTRIBUTES OF SURTI BUFFALO SEMEN AND THEIR INTERRELATIONSHIPS - Chaudhri, DV; Dhami, AJ; Patel, JA; Hadiya, KK (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Forty eight semen ejaculates (8/bull) obtained at weekly interval during the favourable breeding season (November-February) from six mature Surti buffalo bulls of Central Sperm Station of the College under twice a week collection schedule in AV were evaluated for routine physico morphological attributes including motility, viability, morphology (eosin-nigrosin), acrosomal integrity (Giemsa stain) and plasma membrane integrity (HOST 150 mOsm/L). The mean values of ejaculate volume, density (1-4 score), sperm concentration, mass activity (0-5 score), individual sperm motility, live sperm, abnormal sperm, intact acrosome and HOS reactive sperms observed in fresh semen were 3.43±0.10 ml, 2.14±0.11, 744.90± 36.38 million/ml, 3.45±0.07, 78.54±0.51 %, 90.48±0.33 %, 6.15±0.15 %, 94.40±0.20 % and 79.35±0.42 %, respectively. The variation between bulls was significant (P<0.05) for most of these traits. The overall segment-wise per cent abnormalities of sperm head, midpiece and tail region recorded in fresh semen were 1.83±0.09, 0.88±0.06 and 3.44±0.08, respectively. The mean percentages of spermatozoa having swollen, ruffled, detached and denuded acrosome in fresh semen were found to be 2.29±0.08, 1.60±0.10, 1.10±0.09 and 0.60±0.08, respectively. There were significant (P<0.01) interrelationships between sperm motility, viability, normal morphology, intact acrosome and plasma membrane integrity in fresh semen. The findings were within normal physiological limits of the breed, except poor sperm count.